2019
DOI: 10.1073/pnas.1901556116
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting evolution of virulence and replication rate in an emerging bacterial pathogen

Abstract: Host resistance through immune clearance is predicted to favor pathogens that are able to transmit faster and are hence more virulent. Increasing pathogen virulence is, in turn, typically assumed to be mediated by increasing replication rates. However, experiments designed to test how pathogen virulence and replication rates evolve in response to increasing host resistance, as well as the relationship between the two, are rare and lacking for naturally evolving host–pathogen interactions. We inoculated 55 isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 71 publications
(142 reference statements)
1
37
1
Order By: Relevance
“…Here, we attempted to do so in an inoculation experiment of house finches using 55 distinct isolates of their conjunctivitis-causing bacterial pathogen, M. gallisepticum, collected from its emergence (in 1994) and throughout the subsequent 20 years (until 2015) (N = 46 isolates successfully established infection in 47 birds). These isolates have been shown previously to vary in virulence, with later-epidemic isolates causing greater putative host mortality, as well as more severe conjunctival swelling and greater body mass loss than early-epidemic ones (Tardy et al 2019). Further, while this bacterial pathogen has now spread throughout most of the North American house finch range, some western populations have remained unexposed to present day (Staley et al 2018a).…”
Section: Impact Summarymentioning
confidence: 99%
“…Here, we attempted to do so in an inoculation experiment of house finches using 55 distinct isolates of their conjunctivitis-causing bacterial pathogen, M. gallisepticum, collected from its emergence (in 1994) and throughout the subsequent 20 years (until 2015) (N = 46 isolates successfully established infection in 47 birds). These isolates have been shown previously to vary in virulence, with later-epidemic isolates causing greater putative host mortality, as well as more severe conjunctival swelling and greater body mass loss than early-epidemic ones (Tardy et al 2019). Further, while this bacterial pathogen has now spread throughout most of the North American house finch range, some western populations have remained unexposed to present day (Staley et al 2018a).…”
Section: Impact Summarymentioning
confidence: 99%
“…Although it later spread through much of the native western range (between 2000 and 2010; Duckworth et al 2003;Dhondt et al 2006), some populations remain unexposed to date (e.g., in Arizona; Staley et al 2018). We have shown previously that the virulence of M. gallisepticum, defined as the amount of damage done to the house finch host, has increased over the course of the epidemic Tardy et al 2019). Furthermore, we have shown that house finches from exposed populations display less severe symptoms than those from unexposed populations .…”
Section: Box 1: Definitions Predictions and Implications Of Key Termsmentioning
confidence: 99%
“…DNA was extracted using a QIAGEN DNeasy R Blood and Tissue Kit according to the manufacturer's standard protocol (Qiagen, Germany). For each sample, we ran a multiplex quantitative PCR of the M. gallisepticum-specific gene mgc2, which encodes a cytadhesin protein, and the house finch recombination-activation gene rag1, using an Applied Biosystems TM StepOnePlus TM Real-Time PCR system (Applied Biosystems, USA) (Tardy et al 2019). Each reaction contained: 2 µL of sample genomic DNA template, 1 µL each of 10 µM mgc110-F/R, and rag1-102-F/R primers (total 4 µL), 0.5 µL each of 10 µM Mgc110-JOE and Rag1-102-6FAM fluorescent hydrolysis probes (total 1 µL), 10 µL of 2× qPCRBIO Probe Mix HI-ROX (PCR BIOSYS-TEMS) and 3 µL Nuclease-free water (Ambion R , USA).…”
Section: Pathogen Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…The jump of the bacterial pathogen Mycoplasma gallisepticum from its original poultry host into a wild North American songbird in 1994 caused an epidemic so intense that naturally resistant individuals quickly increased in frequency over the subsequent years (through increased survival and/or reproduction). Such rapid spread of host resistance, mediated by immune clearance, was, in turn, found to have driven the rapid evolution of higher pathogen virulence and transmission rates (Tardy et al, 2019). While pathogen evolution in response to host immunity can be challenging to detect in wild populations, similar patterns of evolutionary change can be observed, for example, in response to our use of antibiotics.…”
Section: Barriers To Transmissionmentioning
confidence: 99%